Bone Marrow-Resident Vδ1 T Cells Co-express TIGIT With PD-1, TIM-3 or CD39 in AML and Myeloma - Brauneck, Franziska; Weimer, Pauline; Schulze zur Wiesch, Julian; Weisel, Katja; Leypoldt, Lisa; Vohwinkel, Gabi; Fritzsche, Britta; Bokemeyer, Carsten; Wellbrock, Jasmin; Fiedler, Walter (Frontiers in Medicine, 2021)
Background: γδ T cells represent a unique T cell subpopulation due to their ability to recognize cancer cells in a T cell receptor- (TCR) dependent manner, but also in a non-major histocompatibility complex-(MHC) restricted way via natural killer receptors (NKRs). Endowed with these features, they represent attractive effectors for immuno-therapeutic strategies with a better safety profile and a more favorable anti-tumor efficacy in comparison to conventional αβ T cells. Also, remarkable progress has been achieved re-activating exhausted T lymphocytes with inhibitors of co-regulatory receptors e.g. programmed cell death protein 1 (PD-1), T cell immunoreceptor with Ig and ITIM domains (TIGIT) and of the adenosine pathway (CD39, CD73). Regarding γδ T cells, little evidence is available. This study aimed to immunophenotypically characterize γδ T cells from patients with diagnosed acute myeloid leukemia (AML) in comparison to patients with multiple myeloma (MM) and healthy donors (HD). Methods: The frequency, differentiation, activation, and exhaustion status of bone marrow- (BM) derived γδ T cells from patients with AML (n=10) and MM (n=11) were assessed in comparison to corresponding CD4+ and CD8+ T cells and peripheral blood- (PB) derived γδ T cells from HDs (n=16) using multiparameter flow cytometry. Results: BM-infiltrating Vδ1 T cells showed an increased terminally differentiated cell population (TEMRAs) in AML and MM in comparison to HDs with an aberrant subpopulation of CD27-CD45RA++ cells. TIGIT, PD-1, TIM-3, and CD39 were more frequently expressed by γδ T cells in comparison to the corresponding CD4+ T cell population, with expression levels that were similar to that on CD8+ effector cells in both hematologic malignancies. In comparison to Vδ2 T cells, the increased frequency of PD-1+-, TIGIT+-, TIM-3+, and CD39+ cells was specifically observed on Vδ1 T cells and related to the TEMRA Vδ1 population with a significant co-expression of PD-1 and TIM-3 together with TIGIT. Conclusion: Our results revealed that BM-resident γδ T cells in AML and MM express TIGIT, PD-1, TIM-3 and CD39. As effector population for autologous and allogeneic strategies, inhibition of co-inhibitory receptors on especially Vδ1 γδ T cells may lead to re-invigoration that could further increase their cytotoxic potential.